BLS to publish quarterly data from Consumer Expenditure Survey. - Boyle, Maureen (Monthly Labor Review, 1988)
The Bureau of Labor Statistics will publish quarterly data from the interview portion of its Consumer Expenditure Surveys, beginning with the release of data from the second quarter of 1987. Quarterly estimates based on these data will be presented at annual rates. Quarterly publication will allow earlier availability of data on consumer expenditures and mapping of seasonal trends. A number of seasonal and year-to-year changes observed from 1984 to the first quarter of 1987 are discussed.